MISKONSEPSI MATEMATIKA PADA GURU SEKOLAH DASAR - Ahmad Dzulfikar; Ciptianingsari Ayu Vitantri (Suska Journal of mathematics Education, 2017)
Mathematics concepts in elementary school was basic concepts to understand mathematics concepts in the next grade. Therefore, mathematics misconceptions of elementary school teacher should be avoided. It was because of implication to their students. This study was a qualitative descriptive research. The aim of the study was to investigate mathematics misconceptions of elementary school teacher. Subject of the study was 28 teacher from 17 school in one city in East Java. Purposive sampling was used in the study. Research instrument was a test. Interview was an additional technique to investigate elementary shool teacher mathematics misconceptions and its reason. The study found that mathematics misconceptions of elementary school teacher mostly found in geometry because of preconceptions. Preconceptions mostly affected by a daily meaning. Therefore, development of elementary school teacher mathematics content mastery is needed.